The Role of Ngos In Social Mobilizations: Exploring innovative methods and impact of social mobilization in implementing SGSY (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Itis high time to understand the process of Social Mobilization done by the NGOsin the above said process and implementing SGSY, it is high time to understandand to documents on what are the various methods followed for socialmobilization while implementing SGSY in their respective areas so that if anyinnovative methods used, it can be popularized and used in the future. Hence  the present  study  would be  the  miles stone  for  exploring various  methods used  and  impact made  through  social mobilization for making the SGSY effective and efficient in the future.